THE NECESSITY OF A NEW PARADIGM FOR THE EUROPEAN COHESION POLICY UNDER THE PRESENT GLOBAL CRISIS - Ionescu Romeo (European Regional Science Association (ERSA), 2010)
The present global crisis began in 2007 in the USA. It affected all economies of the world during 2008-2010. Our research deals with the idea of a new paradigm for the European cohesion policy in order to limit and to decrease the regional disparities across the Member States. The paper uses the Eurostat official data base as a neutral approach for all Member States' economies. We talk about the Economic Forecast Spring 2009 of the European Commission, Directorate-General for Economic and Financial Affairs. The analysis is focused on some specific economic indicators (GDP at previous year prices, private consumption, public consumption, gross fixed capital formation, exports, imports, employment, unemployment rate, unit labour costs whole economy, savings rate of households, harmonised index of consumer prices, trade balance, general government gross debt as % of GDP) and covers 2008-2010 period. We used the ranking of the Member States using the method of the relative distances, the ANOVA method (under the unemployment rate) and the cluster analysis, as well. The data processing leads to an unexpected result: the Members States can be easily divided into three categories, each of them with specific evolutions. Moreover, the economic evolution of those Member States' economies leads to greater disparities in 2010, comparing to 2008. These disparities are presented using pertinent diagrams and critical remarks. The question we have to answer is if the present European cohesion policy is able to solve these disparities. Unfortunately, the answer is negative, at least in 2010. As a result, these new socio-economic evolution of the EU under the global crisis represents the real greatest challenge for the EU.
Keywords: 330